"Sustainability vs. Speculation: How ESG Reshapes Stock Market Behavior in ASEAN Plus Three" - Dwi Farid Rahmadhani Azis (Eduvest - Journal of Universal Studies, 2025)
This study examines the impact of Environmental, Social, and Governance (ESG) scores on stock price synchronicity among publicly listed firms in the ASEAN Plus Three (APT) region. Employing panel data analysis over the period 2019–2023, the study investigates how ESG performance influences the extent to which firm-specific information is incorporated into stock prices. The analysis leverages ESG ratings from Refinitiv Eikon and daily stock return data to construct a synchronicity measure based on firm-level regressions. Findings reveal that higher ESG scores are significantly associated with lower stock price synchronicity, indicating enhanced information transparency and reduced information asymmetry. These results underscore the role of ESG integration in improving market efficiency, providing valuable implications for investors, policymakers, and corporate managers in both emerging and developed markets.